Electronic properties of CVD graphene: The role of grain boundaries, atmospheric doping, and encapsulation by ALD. Issue 12 (20th July 2016) - Van Veldhoven, Zenas A.; Alexander‐Webber, Jack A.; Sagade, Abhay A.; Braeuninger‐Weimer, Philipp; Hofmann, Stephan
Abstract : Grain boundaries and unintentional doping can have profound effects on graphene‐based devices. Here we study these in detail for CVD grown poly‐crystalline monolayer graphene with two significantly different grain size distributions centered around 10–25 μm and 100–400 μm. Although the two types of graphene are processed under identical conditions after growth, they show distinct transport properties in field effect transistor devices. While all as‐fabricated samples showed similar p ‐type doping, the smaller grain size type graphene with larger number of grain boundaries exhibit lower average mobility. In order to separate out the effects of grain boundaries and doping from ambient exposure on the transport properties, the devices were encapsulated with Al2 O3 by atomic layer deposition. The encapsulation of large grain samples thereby showed drastic improvements in the performance with negligible doping while the small grain samples are largely intolerant to this process. We discuss the implications of our data for the integrated manufacturing of graphene‐based device platforms.